The Role Of Technical Know-How In Determining The Legal Nature Of A Franchise Contract - El-Haija, Mohammed I Abu (European Scientific Journal, ESJ, 2016)
In view of the importance of a franchise contract in disseminating knowledge, and improvement, this study came to shed light on technical knowledge and its impact on determining the legal nature of a franchise contract. It also illuminated the possibility of the existence of a weak idea or a compliance problem in this type of contract. Strengthening of concession contracts was recommended, particularly relating to the industrial sector, which would inevitably lead to development and prosperity.